Makanan Sebagai Representasi Tradisi Sosial dan Budaya : Kajian Gastrosemiotik Dalam Cerita Rakyat Kuliner - Rochmatul Wachidah, Liana; Setya Yuwana Sudikan; Darni; Anas Ahmadi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to reveal how traditional food not only functions as a story element, but also as a social and cultural marker that contains deep meaning. Food, culture, and identity depicted in literary works reflect the social and cultural dynamics in society. A qualitative descriptive method was used with a focus on literature studies, with data sources from three culinary stories in the Digital Book (BUDI) published by the Ministry of Education and Culture by teachers in Indonesia, namely Nyadran: Learning Tolerance from Tradition, Nasi Berkat, and Tradisi Kupatan. Data collection was carried out through the technique of listening and recording, and data analysis was carried out by data reduction, data presentation, and drawing conclusions/verification. The results of the study show that the three stories have a meaning that is more than just traditional food, but rather a complex representation of the social and cultural traditions of the community. From a gastronomic perspective, this food becomes a "cultural text" that describes the values ​​of solidarity, spirituality, and local wisdom. With Peirce's semiotic approach, this food functions as a sign that strengthens cultural identity, builds social relationships, and awareness of growing social and spiritual. Through ritual ceremonies such as Nyadran, thanksgiving, and kupatan Lebaran, food strengthens relationships between individuals and communities and is a symbol of gratitude and appreciation for others.